RESPECT! SEBAGAI PONDASI DASAR BERPERILAKU MODERAT DI ERA SOCIETY 5.0: Indonesia - Putri Zulfikah; Jihadah Elok Nuril A; Hidayatullah, Ahmad Fauzan; Zakiyah Isnawati; Azizah (Jurnal Dakwah Tabligh, 2023)
Moderate behavior is an attitude that always avoids extreme behavior or disclosure, and is more towards the middle dimension or path. The characteristics of a person being moderate are open, humble, rational thinking, and can provide benefits This study aims to provide knowledge about respect as the basic foundation for moderate behavior and provide an understanding of moderate behavior that will be practiced in everyday life. The research method used is a qualitative library research method. Based on the results of the study, the Pesbukers channel always shows things that involve ridicule, pranks (lying), insults, and even verbal violence which are feared to hurt the children who watch it. it was concluded that the character of a child can be formed from informal education, namely guidance and education from parents, family, and the environment. will tend to affect children, and most of them will think to imitate what they see. Therefore, respect is used as the basic foundation for moderate behavior which is very important to be taught to generations in the era of society 5.0.